Database resources of the National Center for Biotechnology Information in 2025 - Sayers, Eric W; Beck, Jeffrey; Bolton, Evan E; Brister, J Rodney; Chan, Jessica; Connor, Ryan; Feldgarden, Michael; Fine, Anna M; Funk, Kathryn; Hoffman, Jinna; Kannan, Sivakumar; Kelly, Christopher; et al. (Nucleic acids research, 2025)
The National Center for Biotechnology Information (NCBI) provides online information resources for biology, including the GenBank® nucleic acid sequence repository and the PubMed® repository of citations and abstracts published in life science journals. NCBI provides search and retrieval operations for most of these data from 31 distinct repositories and knowledgebases. The E-utilities serve as the programming interface for most of these. Resources receiving significant updates in the past year include PubMed, PubMed Central, Bookshelf, the NIH Comparative Genomics Resource, BLAST, Sequence Read Archive, Taxonomy, iCn3D, Conserved Domain Database, Pathogen Detection, antimicrobial resistance resources and PubChem. These resources can be accessed through the NCBI home page at https://www.ncbi.nlm.nih.gov.